Labour flexibility in the development plan (1999)
Social security is directly related with social and economic aspects and the development plan can influence, through different mechanisms, the coverage and efficacy of the health system. The reform of the recurrent labour legislation aimed at a greater flexibility for the direct hiring of workers and the reduction if the minimum wage can affect the affiliation to the contributory regime and weaken the resources of the subsidized regimen. Evasion and elusion would increase, weakening even more the principles of solidarity.